2010
DOI: 10.1002/jsfa.4227
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and functional properties of a protein isolate produced from safflower (Carthamus tinctorius L.) meal by ultrafiltration

Abstract: In the light of its functional properties found in this study, safflower protein isolate produced by ultrafiltration is recommended for use as an ingredient in food products such as salad dressing, meat products, mayonnaise, cakes, ice cream and desserts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 31 publications
3
34
3
4
Order By: Relevance
“…Typically, at pH's above and below the protein's pI (depending on the magnitude of the charge), the proteins experience electrostatic charge repulsion to keep the proteins from aggregating. In general, the solubility of the concentrates in this study was higher than what has previously been reported for canola protein (Aluko & McIntosh, 2001;Gerzhova et al, 2015), defatted hemp protein isolate (Tang, Ten, Wang, & Yang, 2006), defatted sunflower flour and protein isolate (Lin, Humbert, & Sosulski, 1974), and safflower protein isolate at pH 3 and pH 5 but not pH 7 (Ulloa et al, 2011). The pI for safflower, sunflower, canola, and hemp in the present study was 5.…”
Section: Solubilitycontrasting
confidence: 68%
See 2 more Smart Citations
“…Typically, at pH's above and below the protein's pI (depending on the magnitude of the charge), the proteins experience electrostatic charge repulsion to keep the proteins from aggregating. In general, the solubility of the concentrates in this study was higher than what has previously been reported for canola protein (Aluko & McIntosh, 2001;Gerzhova et al, 2015), defatted hemp protein isolate (Tang, Ten, Wang, & Yang, 2006), defatted sunflower flour and protein isolate (Lin, Humbert, & Sosulski, 1974), and safflower protein isolate at pH 3 and pH 5 but not pH 7 (Ulloa et al, 2011). The pI for safflower, sunflower, canola, and hemp in the present study was 5.…”
Section: Solubilitycontrasting
confidence: 68%
“…Due to the limited number of data points collected, these values represent an imprecise approximation of the pI only. As measured by solubility curves, the pI of safflower was reported as between pH 4 and pH 5 (Ulloa et al, 2011) and hemp protein isolate at pH 5 (Tang, Ten, Wang, & Yang, 2006) corresponding to the pHs where minimum solubility was found. Shchekoldina and Aider (2014) reported a sunflower protein isolate to have a pI of 4.7.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest bulk density was found in protein isolates from Mash 1-1 cultivar while the highest bulk density was found in protein isolates from T-9. Our results showed lower values than safflower protein isolates which have bulk density of 0.27 g/mL (Ulloa, Rosas-Ulloa, & Ulloa-Rangel, 2011) and freeze dried lentil protein isolates having bulk density of 0.28 g/mL (Joshi, Adhikari, Aldred, Panozzo, & Kasapis, 2011). Statistical analysis indicated that hydrolysed black gram protein isolates had significantly (p 0.05) lower bulk density than native protein isolates.…”
Section: Bulk Densitymentioning
confidence: 47%
“…The nature of proteins (i.e., composition of charged, non‐charged, polar and non‐polar amino acid residues) that possess hydrophilic and hydrophobic properties, thus interacting with both water and oil components could be used as emulsifiers in food systems. Oil‐in‐water emulsion formation is based on the adsorption of proteins at the surface of oil droplets in the form of a densely packed layer and are largely dependent on protein solubility and hydrophobicity (Ulloa, Rosas‐Ulloa, & Ulloa‐Rangel, ). The emulsion capacity (43.71%–66.90%) and stability (64.36%–80.15%) was found significantly different ( p < .05).…”
Section: Resultsmentioning
confidence: 99%